Wireless Network Bandwidth Quality Measurement Using Qos Standard Tiphon - Ahmad Basri; Boy Yuliadi (PIKSEL : Penelitian Ilmu Komputer Sistem Embedded and Logic, 2023)
As technology develops, computer networks have a very important role because they have many advantages, such as ease and efficiency. In designing research on bandwidth quality on wireless LAN networks at the Baidhaul Ahkam Islamic Education Foundation, the method used is the Network Development Life Cycle (NDLC) and has several stages, namely Analysis, Design, Simulation Prototyping, implementation, Monitoring, and Management. This research will analyze the quality of bandwidth on wireless LAN networks at the Baidhaul Ahkam Islamic Education Foundation using the QoS (Quality of Service) method of tiphon standards. The results of the measurements obtained will then be processed and analyzed to provide value information, Throughput, Packet Loss, Delay, and Jitter used to describe or evaluate the quality of the wireless LAN network that has been provided. The quality of bandwidth traffic at the Baidhaul Ahkam Islamic Education Foundation can be seen from each throughput value of 938k, Packet Loss of 0%, delay of 2.784333 ms, and jitter of 2.76 These values are included in the excellent category. From these results, it can be concluded that the bandwidth available today still meets the needs of internet use at the Baidhaul Ahkam Islamic Foundation